2024
DOI: 10.3389/fimmu.2023.1331151
|View full text |Cite
|
Sign up to set email alerts
|

The regulatory role of eosinophils in adipose tissue depends on autophagy

Aref Hosseini,
Nina Germic,
Nikita Markov
et al.

Abstract: IntroductionObesity is a metabolic condition that elevates the risk of all-cause mortality. Brown and beige adipose tissues, known for their thermogenic properties, offer potential therapeutic targets for combating obesity. Recent reports highlight the role of immune cells, including eosinophils, in adipose tissue homeostasis, while the underlying mechanisms are poorly understood.MethodsTo study the role of autophagy in eosinophils in this process, we used a genetic mouse model lacking autophagy-associated pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…In this regard, Jansen et al (2012) have demonstrated that the inhibition of autophagy increases the gene expression and secretion of proinflammatory cytokines, including interleukin (IL)-1β, IL-6, and IL-8 in the adipocytes of obese people and in the adipose tissue of obese mice, thus suggesting that autophagy may dampen excessive inflammation in adipose tissue during obesity. Moreover, in a very recent study ( Hosseini et al, 2024 ) the authors investigated the role of autophagy in eosinophils, immune cells strongly involved in adipose tissue homeostasis. They used a genetic mouse model lacking Atg5 specifically within the eosinophils and they observed that the absence of Atg5 was associated with an increase in body weight and alterations of the adipose tissue cellular architecture.…”
Section: Obesitymentioning
confidence: 99%
“…In this regard, Jansen et al (2012) have demonstrated that the inhibition of autophagy increases the gene expression and secretion of proinflammatory cytokines, including interleukin (IL)-1β, IL-6, and IL-8 in the adipocytes of obese people and in the adipose tissue of obese mice, thus suggesting that autophagy may dampen excessive inflammation in adipose tissue during obesity. Moreover, in a very recent study ( Hosseini et al, 2024 ) the authors investigated the role of autophagy in eosinophils, immune cells strongly involved in adipose tissue homeostasis. They used a genetic mouse model lacking Atg5 specifically within the eosinophils and they observed that the absence of Atg5 was associated with an increase in body weight and alterations of the adipose tissue cellular architecture.…”
Section: Obesitymentioning
confidence: 99%